What moves households' expectations during a crisis? Evidence from a randomized information experiment - Norbert Metiu; Valentin Stockerl (Deutsche Bundesbank, 2024)
Using a randomized information experiment embedded in a representative survey, we study households' economic expectations at onset of the COVID-19 crisis. Our experimental evidence indicates that households are not fully aware of what is happening in the economy shortly after the pandemic outbreak. Households that receive information on experts' views on the economy become more pessimistic and uncertain about the economic outlook and less willing to consume. Surprisingly, this also holds for households that receive information on major monetary and fiscal stimulus measures announced in response to the COVID-19 crisis, suggesting that policy announcements convey bad news about the economy that overshadow the good news about the measures announced. The effects are driven by households who are less exposed to and less informed about the economic consequences of the pandemic, underscoring that personal experiences receive a large weight in household expectation formation.
Keywords: D12; D83; D91; E58; G11; 330; household expectations; beliefs; information; policy announcements; randomized information experiment; COVID-19